2021
DOI: 10.2463/mrms.mp.2019-0201
|View full text |Cite
|
Sign up to set email alerts
|

Peritumoral Fat Content Correlates with Histological Prognostic Factors in Breast Carcinoma: A Study Using Iterative Decomposition of Water and Fat with Echo Asymmetry and Least-Squares Estimation (IDEAL)

Abstract: Purpose: To correlate peritumoral fat content using iterative decomposition of water and fat with echo asymmetry and least-squares estimation (IDEAL) with histologic prognostic factors in breast carcinoma. Materials and Methods:This study consisted of 100 patients who were diagnosed with invasive carcinoma of breast and underwent breast MRI including IDEAL before surgery. The scan time of IDEAL fat fraction (FF) map imaging was 33 s. Four regions of interests (ROIs), which are a distance of 5 mm from the tumor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…Altered adipocytes promote the growth, invasion, and metastasis of breast cancer cells and induce an inflammatory microenvironment in the peritumoral adipose tissue (AT) [ 12 , 13 ]. Previous studies reported that the adipocyte alterations in peritumoral breast AT can be evaluated via imaging features of CT and magnetic resonance imaging (MRI) [ 15 , 16 , 17 ]. Further, these imaging features of peritumoral breast AT based on CT and MRI were significantly associated with axillary lymph node metastasis [ 15 , 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Altered adipocytes promote the growth, invasion, and metastasis of breast cancer cells and induce an inflammatory microenvironment in the peritumoral adipose tissue (AT) [ 12 , 13 ]. Previous studies reported that the adipocyte alterations in peritumoral breast AT can be evaluated via imaging features of CT and magnetic resonance imaging (MRI) [ 15 , 16 , 17 ]. Further, these imaging features of peritumoral breast AT based on CT and MRI were significantly associated with axillary lymph node metastasis [ 15 , 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies reported that the adipocyte alterations in peritumoral breast AT can be evaluated via imaging features of CT and magnetic resonance imaging (MRI) [ 15 , 16 , 17 ]. Further, these imaging features of peritumoral breast AT based on CT and MRI were significantly associated with axillary lymph node metastasis [ 15 , 16 , 17 ]. The interaction between breast cancer cells and AT leads to enhanced glycolysis of adipocytes and inflammation in peritumoral AT [ 12 , 14 ], suggesting that peritumoral breast AT might also exhibit distinct FDG PET/CT features in patients with breast cancer, which could also have a significant association with tumor invasiveness and metastasis.…”
Section: Introductionmentioning
confidence: 99%